Navigating the maze of deception in endurance sports: A systematic review - De Lucia, B. J.; Hutchinson, J. C.; Bottino, A. (Perceptual and Motor Skills, 2025)
Endurance exercise bouts require sustained exertion and the precise regulation of energy expenditure. Without accurate knowledge of the task demands and performance metrics (e.g., speed, distance), individuals may struggle to establish or maintain effective pacing strategies. Providing deceptive information about the task can be a useful experimental tool for exploring the phenomenon of pacing and endurance performance. The purpose of this systematic review was to synthesize existing research on the effect of deception on performance outcomes in endurance sport tasks. An electronic search was performed across four databases and 21 studies met the inclusion criteria for the review. Studies investigated deception of time, split pace, power output, anticipated difficulty, speed, previous performance, and presence of a competitor within cycling, running, and/or triathlon tasks. Various methodologies, including different types and percentages of deception, were utilized across studies in review. Time deception does not appear to influence cycling performance but may influence pacing strategy. Competitor deception appears to improve endurance performance, however the effects of speed and power deception had conflicting findings within the literature. Due to the discrepancies across studies and most studies using male cyclists, future research should consider the effects of deceptive feedback in other endurance tasks as well as in more diverse samples and utilizing mixed-method designs.